Intersectoral action for health : Sri Lanka study. - Marga Institute (Colombo, Sri Lanka : Marga Institute, 1984)
Study based on 1980 data.
Includes statistical tables.
Keywords: Public health -- Sri Lanka; Sri Lanka -- Economic conditions; Sri Lanka -- Social conditions